Phytochemical screening and characterization of Meliadubia leaves extract for antimicrobial activity against Escherichia coli staphylococcus and aureus - Mustafa, Mudhafar; Ismail, Zainol; Jaafar, C. N. Aiza; H. A., Alsailawi; Arkan, Majhool Alhussein; M. B., Alsaady Mofaq (Indian Ecological Society, 2020)
In this study, the leaves of Meliadubia were extracted through the hot-extraction method using distilled water as a solvent. The crude extract of M. dubia was evaluated for their chemical group compounds using phytochemical screening for the chemical group compounds. Meanwhile, Gas chromatography (GC), Energy-dispersive X-ray spectroscopy (EDX) and Fourier-transform infrared spectroscopy (FTIR) were used to conform to the fictional groups in the leave of M. dubia. Phytochemical screening analysis was done using common procedures and had shown the presence of alkaloids, carbohydrates, tannins, steroids, and flavonoids. Twenty-two compounds were identified in the GC-Mass spectrometry. The highest compounds were Pyridine, 2,3,4,5-tetrahydro-3-methyl (17.03%), 1-azabicyclo (3.1.0) hexane (12.16%), and 2-Undecanol (7.63%), while the lowest compounds were Heptafluorobutyric acid, n-tetradecyl ester (0.79%) and 4-Methyl-3-pentenal (0.79%). The EDX analysis presented two elements, which were carbon (53%) and oxygen (46%). The M. dubia band at 1668 cm−1 refers to the amide I C=O stretching, and the peak at 2140 cm−1 is associated to the alkyne group that exists in the phyto-constituents of M. dubia extract. Meanwhile, the peak that was monitored at 3301 cm−1 corresponds to the amide A (N-H). The observed peaks are mainly discovered as flavanoids and terpenoids that exist significantly in the plant extract. The antibacterial activities investigated against gram-negative bacteria, Escherichia coli E.coli) and gram-positive bacteria, Staphylococcus aureus (S. aureus). The results had presented the factional activity for M. dubia against both pathogens.